The importance of small decisions : how culture evolves - O'Brien, Michael J., (Simplicity, 2019)
How people make decisions in an era of too much information and fake news. Humans originally evolved in a world of few choices. Prehistoric, preindustrial, and predigital eras required fewer decisions than today's all-access, always-on world of too much information. Economists have largely discarded the idea that agents act rationally and the market follows suit. It seems that no matter how small or innocuous a decision might seem, there's almost no way to guess the effect it might have. The authors of The Importance of Small Decisions view decisions and their outcomes from a different perspective: as key elements in the evolution of culture. In this trailblazing book, they examine different kinds of decisions and map the outcomes, both short- and long-term. Drawing on this, they introduce a map of social behavior that captures the essential elements of human decision-making. The authors look at the New England Patriots' decision in 2000 to draft an underachieving college quarterback named Tom Brady; they consider Warren Buffett's investment strategy; and they chart the 'dancing landscape' of a college applicant's decision-making environment. Finally, they show that decisions can be ranked according to transparency of choice and social influence. When fake news seems indistinguishable from real news and when the internet offers a cacophony of voices, they warn, we can't afford to crowdsource our decisions.